CYBERBULLYING: STUDENT’S BEHAVIOR IN VIRTUAL WORLDS - Wangid, Muhammad Nur (Universitas Muhammadiyah Metro, 2016)
Abstract: Concerning about student’s negative behaviors in using of the internet encouraged the survey to describe the behavior of students in the virtual world. The sample consisted of 497 students, consisting of 336 women and 161 men, taken by proportional random sampling. Instruments of data collection using questionnaire. The results showed that mobile phones become the primary tool in the move to the internet is more widely used to send the message. Using internet lasting for more two hours per day, and carried anywhere. Activities at home is higher than the on-campus in the surf. Most students use the internet to find the source of the task, followed by activities on facebook. Three major forms of cyberbullying behaviors students were outing, flaming and harassment. While experience as a victim of cyberbullying was in the form of flaming, harassment, and cyber-stalking.Keywords: cyberbullying; students behavior